El danzante de Pujilí - Quevedo Quevedo, Cristian Fernando (2020)
Ecuador has cultural diversity, with festivals, celebrations, and characters that are artistic expressions of our culture; these are testimony of multiculturalism, with the heritage of the Inca Empire and the Spaniards' arrival with the Catholic religion. Those characteristics features are expressed in the festivity of Corpus Christi, with "El danzante de Pujilí"; this is the leading figure of this celebration for the symbolism and color it represents. This research aimed to determine the roots, the meaning, and changes that have occurred over time. The analysis of documentation and interviews, i.e., the study used quantitative methodology carried out to more specific aspects; bibliographic research is part of the pre-Inca period's most outstanding cultural traits. "El danzante de Pujilí character is synonymous of religion, which constituted a cultural syncretism detailed in the elements and characters that revolve around it. Besides, the research highlights all the aspects and characteristics surrounding the dancer as an intangible heritage of the nation. This study's impact intends to have an approach more accurate to the origin of "El danzante de Pujilí" with cultural syncretism.